Diurnal changes of photosynthesis and growth of Arthrospira platensis cultured in a thin-layer cascade and an open pond - Silva Benavides, Ana Margarita (2017)
Diel changes in photosynthetic performance and biomass productivity were thoroughly examined in Arthrospira platensis cultures grown outdoors in an open circular pond (OCP) and a thin-layer cascade (TLC). The two cultures were grown at the same areal biomass density, but temperature maxima were adjusted to optimal (33 °C) and suboptimal (25 °C). At the optimal temperature, the cultures grown in TLC showed about 20% higher photosynthetic activity than those in OCP, while at the suboptimal one photosynthetic activity dropped by 20% and 35% in the TLC and OCP, respectively. Accordingly, the highest biomass productivity over 20 g m− 2 d− 1 was attained in the TLC at the optimal temperature, while at the suboptimal temperature the productivity decreased by 20%. In the OCP, the biomass productivity at both temperatures was about one third lower compared to those in the TLC. The better culture performance in the TLC was mainly ascribed to the shorter light path that promoted much faster light/dark cycles favourable for photosynthesis, as well as the faster warming of the cultures in the morning as compared to the OCP cultures. Monitoring photosynthesis performance of a culture can indicate design improvements, which may capitalize this photochemical advantage, increasing biomass productivity further.